Studies in management information - Bishop, Stanley Victor; Institute of Chartered Accountants in England and Wales, London (London : Institute of Chartered Accountants in England and Wales (General Educational Trust), 1969)
This book is addressed to managers-accountants and otherwise-who are dedicated to achieving outstanding results, in the belief that it will suggest better ways of determining what this results should be, and more certain methods of ensuring that they are achieved.
First published as numbers 1-8 of Management information.
Includes bibliographical references and index.
hza 21/09/2018
Loans
Keywords: Industrial management; Accounting; Management information systems